Differential GR Expression and Translocation in the Hippocampus Mediates Susceptibility vs. Resilience to Chronic Social Defeat Stress - Han, Qiu-Qin; Yang, Liu; Huang, Hui-Jie; Wang, Ya-Lin; Yu, Rui; Wang, Jing; Pilot, Adam; Wu, Gen-Cheng; Liu, Qiong; Yu, Jin (Frontiers in Neuroscience, 2017)
While social stress exposure is a common risk factor for affective disorders, most individuals exposed to it can maintain normal physical and psychological functioning. However, factors that determine susceptibility versus resilience to social stress remain unclear. Here, the resident-intruder model of social defeat was used as a social stressor in male C57BL/6J mice to investigate the difference between susceptibility and resilience. As depression is often characterized by hyperactivity of the hypothalamic-pituitary-adrenal (HPA) axis, we conducted the present study to further investigate the individual differences in the HPA axis response and glucocorticoid receptor (GR) protein expression and translocation between susceptible mice and resilient mice. We found that hypercortisolemia, induced by social defeat stress occured in susceptible mice, but not in resilient mice. Moreover, susceptible mice exhibited significantly less GR protein expression and nuclear translocation in the hippocampus than resilient mice. Treatment with escitalopram could decrease the serum corticosterone (CORT), increase GR protein expression as well as nuclear translocation in the hippocampus and ultimately reverse social withdrawal behaviors in susceptible mice. These results indicate that the up-regulation of GR and the enhancement of GR nuclear translocation in the hippocampus play an important role in resilience to chronic social defeat stress.